N.G. Barrier y V.A. Dusenbery (comps.), The Sikh Diaspora, Migration and the Experience beyond Punjab, Columbia, South Asia Publications, 1989: x + 352 pp. - Devalle, Susana B. C. (Estudios de Asia y África, 1991)
-